Intravenous high-dose immunotherapy: practical recommendations for use in the treatment of neurological disimmune diseases - N. A. Suponeva; D. A. Grishina (Нервно-мышечные болезни, 2015)
Current publication summarizes main indications and benefits of intravenous high-dose immunotherapy (IHI) in the treatment of various autoimmune diseases of the peripheral nervous system. Available products of intravenous immunoglobulin (IVIG) on the Russian market are reviewed. Tactics for choosing optimal medication for IHI based on its effectiveness and safety are analyzed. Dosage calculation and way of administration of IVIG are described, beeing of a high practical value in neurologist’s daily work.